Longphongtook – an Indigenous Tribal Fishing Technique in Fast Flowing Rivers of Arunachal Pradesh, India - Dutta, R.; Bhagabati, S. K.; Mili, K.; Bhuyan, P. C.; Kumar, A.; Songtheng, P.; Borah, S. (Fishery Technology, 2019)
Longphongtook an indigenous fish aggregating method practised along the Namsang stream by Nocte tribe of Tirap district of Arunachal Pradesh has been described in the present study. In this practice, fishes were caught by attracting them to a circular structure (diameter 2.5 to 2.75 m) made up of boulders and pebbles of the river bed. The study revealed that thigmotropism behaviour of fish was effectively and efficiently utilised by the fisher folk in this fishing technique. The catch mostly comprised of migratory hill stream fishes.